Benefits of Music Therapy in the Quality of Life of Older Adults (2019)
Introduction: Aging is a complex, universal and irreversible process, with gradual changes that fluctuate from one person to another due to several factors (physiological, biological, environmental, social etc.). There are precedents for the potential effect of music therapy on psychological and social aspects which are characteristic of the elderly. In this sense, the aim of this work is to evaluate the effectiveness of music therapy in improving the quality of life of older adults. Materials and Methods: A quality of life inventory was administered, comparing a group that attended a music therapy stimulation and a control group that did not have this type of stimulus. Results: Music therapy attendees had higher scores in terms of total quality of life and subcomponents of the inventory (religion, creativity, recreation and love). Conclusion: The music therapy approach, with its non-invasive techniques, presents a proposal with potential benefits to improve the quality of life of the elderly.